MR-compatibility assessment of MADPET4: a study of interferences between an SiPM-based PET insert and a 7 T MRI system. (30th April 2018) - Omidvari, Negar; Topping, Geoffrey; Cabello, Jorge; Paul, Stephan; Schwaiger, Markus; Ziegler, Sibylle I
Abstract: Compromises in the design of a positron emission tomography (PET) insert for a magnetic resonance imaging (MRI) system should minimize the deterioration of image quality in both modalities, particularly when simultaneous demanding acquisitions are performed. In this work, the advantages of using individually read-out crystals with high-gain silicon photomultipliers (SiPMs) were studied with a small animal PET insert for a 7 T MRI system, in which the SiPM charge was transferred to outside the MRI scanner using coaxial cables. The interferences between the two systems were studied with three radio-frequency (RF) coil configurations. The effects of PET on the static magnetic field, flip angle distribution, RF noise, and image quality of various MRI sequences (gradient echo, spin echo, and echo planar imaging (EPI) at 1 H frequency, and chemical shift imaging at 13 C frequency) were investigated. The effects of fast-switching gradient fields and RF pulses on PET count rate were studied, while the PET insert and the readout electronics were not shielded. Operating the insert inside a 1 H volume coil, used for RF transmission and reception, limited the MRI to T1-weighted imaging, due to coil detuning and RF attenuation, and resulted in significant PET count loss. Using a surface receive coil allowed all tested MR sequences to be used with the insert, with 45–59% signal-to-noise ratio (SNR) degradation, compared to without PET. With a 1 H/ 13 C volume coil inside the insert and shielded by a copper tube, the SNR degradation was limited to 23–30% with all tested sequences. The insert did not introduce any discernible distortions into images of two tested EPI sequences. Use of truncated sinc shaped RF excitation pulses and gradient field switching had negligible effects on PET count rate. However, PET count rate was substantially affected by high-power RF block pulses and temperature variations due to high gradient duty cycles.